Comparative Anatomy of Mitral and Tricuspid Valve: What Can the Interventionlist Learn From the Surgeon - Pozzoli, Alberto; Zuber, Michel; Reisman, Mark; Maisano, Francesco; Taramasso, Maurizio (Frontiers in Cardiovascular Medicine, 2018)
Transcatheter valve interventions on the mitral and tricuspid valves provide currently increasing complexity. Part of the experience and knowledge that has been generated during the development of mitral devices can be adopted for the tricuspid valve. However, a deep understanding of the peculiar anatomy of the tricuspid and of the right heart chambers, with differences and similarities between the two valves results today essential. This review explores anatomical similarities and differences between the mitral and tricuspid valve, illustrating surgical anatomy, and their inferences with regard to transcatheter treatments.